2017
DOI: 10.1021/acs.inorgchem.7b00041
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Structure of a LiB3O5–Li2Mo3O10 High-Temperature Solution for Understanding the Li2Mo3O10 Flux Behavior

Abstract: LiB3O5 is the most widely used nonlinear optical crystal. Li2Mo3O10 (a nominal composition) is a typical flux used to produce large-sized and high-quality LiB3O5 crystals. The structure of the LiB3O5–Li2Mo3O10 high-temperature solution is essential to understanding the flux behavior of Li2Mo3O10 but still remains unclear. In this work, high-temperature Raman spectroscopy combined with density functional theory (DFT) was applied to study the LiB3O5–Li2Mo3O10 solution structure. Raman spectra of a LiB3O5–Li4Mo5O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The Li 2 GeO 3 crystal is characterized by a high piezoelectric constant (5 times as large as that of α-quartz), larger pyroelectric constants (about 5 times as large as that of tourmaline), moderate mechanical impedance, and transparency in the visible region and thus can be used in various piezoelectric, pyroelectric, and acousto-optic devices. , In addition, recent research has demonstrated that the porous Li 2 GeO 3 electrode has superior electrochemical performance and thus great potential for energy storage . Li 2 GeO 3 crystals are often grown from Li 2 GeO 3 high-temperature melts. , The crystal performance is deteriorated by defects such as twinning structure and flaws in the core. , Knowledge of the melt structure at the molecular level is important in understanding the melt physicochemical properties, , which will help us to select optimum conditions to control the crystal growth and eventually to improve the crystal quality …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Li 2 GeO 3 crystal is characterized by a high piezoelectric constant (5 times as large as that of α-quartz), larger pyroelectric constants (about 5 times as large as that of tourmaline), moderate mechanical impedance, and transparency in the visible region and thus can be used in various piezoelectric, pyroelectric, and acousto-optic devices. , In addition, recent research has demonstrated that the porous Li 2 GeO 3 electrode has superior electrochemical performance and thus great potential for energy storage . Li 2 GeO 3 crystals are often grown from Li 2 GeO 3 high-temperature melts. , The crystal performance is deteriorated by defects such as twinning structure and flaws in the core. , Knowledge of the melt structure at the molecular level is important in understanding the melt physicochemical properties, , which will help us to select optimum conditions to control the crystal growth and eventually to improve the crystal quality …”
Section: Introductionmentioning
confidence: 99%
“…1,5 Knowledge of the melt structure at the molecular level is important in understanding the melt physicochemical properties, 6,7 which will help us to select optimum conditions to control the crystal growth and eventually to improve the crystal quality. 8 Previous research has shown that the Li 2 GeO 3 melt has two possible structures. Voron'ko et al inferred that the melt is made up of [GeO 2 Ø 2 ] n chains (GeO 2 Ø 2 tetrahedra connected with each other by sharing bridging oxygen, denoted by Ø) by comparison of the Raman spectrum of the Li 2 GeO 3 melt to that of the Li 2 GeO 3 crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the melt spectra changed systematically with an increase in the MoO 3 content but subtly upon a further addition of MoO 3 into a MoO 3 -rich melt such as K 2 Mo 3 O 10 . Similar spectral characteristics were also observed as we studied the spectra of Li 2 Mo n O 3 n +1 ( n = 1, 2, 3, and 4) melts . Voronko et al deemed that the spectral changes arose from a series of structural changes.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles calculation provides a means to simulate the Raman spectrum of a melt with an established structure and is an effective tool for aiding the experimental analyses of various melt Raman spectra and structures. Recently, Wang and co-workers studied the Raman spectra of the K 2 Mo n O 3 n +1 ( n = 1, 2, and 3) melts with the restricted Hartree–Fock (RHF) method, and we studied the Raman spectra of the Li 2 Mo n O 3 n +1 ( n = 2 and 3) melts with the density functional theory (DFT) method . However, the Raman spectra of alkali molybdate melts rich in MoO 3 , such as alkali tetramolybdate melts, still remain unexplored, although they are especially important to unraveling the subtle spectral characteristics of MoO 3 -rich melts and then to determine the composition–structure relationship of alkali molybdate melts.…”
Section: Introductionmentioning
confidence: 99%
“…In order to eliminate the anharmonic effect [ 56,57 ] induced by high temperatures, all samples are compared at the same temperature of 1273 K. Based on our experiments, the W–O nb characteristic symmetric stretching vibration wavenumbers of the four‐coordinated W–O complex vary with melt compositions A 2 W n O 3n + 1 as shown in Figure 4. The corresponding major W–O complex existing in melt stably is the isolated [WO 4 ] 2− ( Q 0 ), [ 27 ] [W 2 O 7 ] 2− dimer (2 Q11), [ 23,24,29 ] and [W 3 O 10 ] 2− trimer ( 2Q12 and Q211), [ 30–32 ] respectively, for n values of 1, 2, and 3. This is consistent with the trend shown in Figure 2, namely, v ( Q 0 ) < v ( Q11) < v ( Q12) < v ( Q211).…”
Section: Resultsmentioning
confidence: 99%